Pre-harvest shading treatment effects on post-harvest mealiness of ‘Forelle’ pear - Dippenaar, Liza-Mari (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.